Taxation, e-commerce and determination of permanent establishment / Zaleha Othman and Mustafa Mohd Hanefah - Othman, Zaleha; Mohd Hanefah, Mustafa (Accounting Research Institute (ARI) & Faculty of Accountancy, 2006)
E-commerce provides a new way of conducting commercial transactions in today’s global market. E-commerce has made the world a one big marketplace. However, e-commerce also poses challenges to the existing tax rules in determining permanent establishment of businesses. Permanent establishment has been used as the criteria to determine whether a country has taxing rights on the business profits of a non-resident taxpayer. Most tax experts view the current concept of permanent establishment as insufficient to cope with e-commerce, as it is seen to be more suitable for traditional business transactions rather than internet trading. This paper investigates the application of current tax laws in Malaysia on the determination of permanent establishment in an e-commerce environment. Implications of existing policy to establish the source of income in e-commerce are also explored. Interviews were conducted to solicit opinions of tax officers and tax professionals in Malaysia. The respondents agree that the criteria used to determine permanent establishment should be applicable to both types of transactions: conventional and e-commerce. However, the respondents perceived that additional criteria should be included to determine permanent establishment in e-commerce transactions and some modifications to its definition are necessary to suit the modern form of trading over the internet.